SUBJECT- AND RESOURCE-SPECIFIC MONITORING AND PROACTIVE MANAGEMENT OF PARALLEL RF TRANSMISSION - Deniz, Cem M. (Magn Reson Med, 2015)
PURPOSE: Develop a practical comprehensive package for proactive management of parallel RF transmission. METHODS: With a constrained optimization framework and predictive models from a pre-scan based multi-channel calibration, we presented a method supporting design and optimization of parallel RF excitation pulses that accurately obey the forward / reflected peak and average power limits of the RF power amplifiers in parallel transmit imaging experiments and Bloch simulations. Moreover, local SAR limits were incorporated into the parallel RF excitation pulses using electromagnetic field simulations. Virtual transmit coils concept for minimization of reflected power (effecting subject-specific matching) was additionally demonstrated by leveraging experimentally calibrated power models. RESULTS: Incorporation of experimentally calibrated power prediction models resulted in accurate compliance with prescribed hardware and global SAR limits. Incorporation of spatial average 10g SAR models, facilitated by simplifying numerical approximations, provided assurance of patient safety. RF pulses designed with various constraints demonstrated excellent excitation fidelity -- the NRMSE of the simulated excitation profiles was 2.6% for the fully constrained pulses, comparable to that of the unconstrained pulses. An RF shimming example showed a reduction of the reflected-to-forward power ratio to 1.7% from a conventional approach’s 8.1%. CONCLUSIONS: Using the presented RF pulse design method, effective proactive management of the multifaceted power and SAR limits was demonstrated in experimental and simulation studies.